Characteristic social innovation and social novelty as a category of sustainable development - Bui Yuliia; Буй Юлія; Ivanna Melnychuk; Мельничук Іванна (ФОП Сабов А. М., 2019)
Abstract. Conceptual interpretation of social innovation emerged in the first half of the XX-th century at the stage of development of socioeconomic science. The concept of social innovation found its wide reflection in management theory, fundamentals of marketing and business innovation strategies. It should be noted that way back John Galbraith stressed upon the limited potential of scientific-and-technological advance in social life of a community and warned that excessive progress in science and technology could cause a number of negative implications for both humanity and environment. The development of economic systems and relationship between market participants are influenced not only by economic forces, but also by social, political, psychological and ethical issues. Another famous economist – Peter Ferdinand Drucker – claimed that not only science or technology generated new knowledge and devalued traditional practices. It is not infrequent that social innovation turns out to be of greater importance than scientific ones. P. Drucker was the first to discover that the most significant among all the contemporary world outlook transformations was the belief that «during the previous 40 years’ steady innovation, both technological and social, has become in and of itself a new structured scientific discipline, that should be taught and which should be investigated».
Характеристика соціальних інновацій та соціальної новизни як категорій сталого розвитку
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: sustainable development; social innovation